Genome-wide association studies in rice germplasm reveal significant genomic regions for root and yield-related traits under aerobic and irrigated conditions - Padmashree, Revadi; Barbadikar, Kalyani M.; Honnappa,; Magar, Nakul D.; Balakrishnan, Divya; Lokesha, R.; Gireesh, C.; Siddaiah, Anantha M.; Madhav, Maganti Sheshu; Ramesha, Y. M; Bharamappanavara, Muralidhara; Phule, Amol S.; et al. (Frontiers in Plant Science, 2023)
Development of nutrient-use efficient rice lines is a priority amidst the changing climate, depleting resources viz., water, land, and labor for achieving sustainability in rice cultivation. The dry direct-seeded aerobic system of rice cultivation is gaining ground as a water-saving technology along with the traditional transplanted irrigated system. The root-related traits play a crucial role in nutrient acquisition, adaptation to stress and need to be studied along with the yield-attributing traits. We phenotyped a panel of rice germplasm consisting of 118 diverse rice lines for seedling vigor index (14 and 21 days), root-related traits at panicle initiation stage in polythene bags under controlled aerobic condition; yield and yield-related traits under irrigated and aerobic conditions at ICAR-IIRR, Hyderabad and ARS, Dhadesugur, Raichur, Karnataka. The panel was genotyped using SSR markers and genome-wide association studies were conducted for identifying marker-trait associations (MTA). Significant correlations were recorded for root length, root dry weight with the seedling vigour, and with root volume at the panicle initiation stage. The panel was divided into three sub-groups (k=3) and correlated with the principal component analysis (PCA). The total number of grains showed a significant correlation with grain yield per plant along with two MTAs (RM22961, RM1146) under aerobic conditions. A total of 59 common MTAs were detected when analyzed in both GLM and MLM, whereas 78 significant marker associations were detected when analyzed only in MLM. The maximum number of MTAs were found on chromosomes 2, 3, and 12 with phenotypic variability ranging between 0.103 (RM1388) to 0.243 (RM20698). The in-silico analysis identified genes associated to abiotic stress, such as NAM, LEA, and BRI-1, were located close to the markers, indicating a significant association of markers with root and yield-related traits influencing. The identified lines having high seedling vigour index (Langphou, TI-128, Mouli and JBB-631-1), high yield under aerobic condition (Phouren, NPK-43, JBB-684 and Ratnamudi), high root length (MoirangPhou-Angouba, JBB-661, Dissi and NPK-45), root volume (Ratnachudi, KJ-221, Mow and PUP-229) can be further employed in breeding programs. The identified MTAs and the rice lines can be deployed for improving yield, seedling vigour and adaptability for water-saving technologies.